Evaluation of serum uric acid among new-onset primary hypertension patients - A cross-sectional study - Rani Ghali; Arif Maldar; Pournima Patil; Romana Khursheed (Wolters Kluwer Medknow Publications, 2022)
Background: Hypertension is associated with a myriad of confounding factors, out of which elevated serum uric acid (SUA) profile is of interest as a biomarker. Despite a handful of studies alluding to the seminal relationship between the two, its prevalence and correlation in the Indian context have not been adequately investigated. Hence, the present study was aimed to evaluate the relationship between SUA levels and primary hypertension (HTN). Materials and Methods: This 1-year hospital-based cross-sectional study comprised 100 patients who were recently diagnosed with primary HTN and had not received antihypertensive medications, SUA levels and severity of HTN among patients were assessed along with their age, sex, body mass index, total cholesterol, and lipid profile. Results were statistically analyzed by Chi-square test, logistics regression, t-test/Welch t-test/Mann-Whitney U-test, and Pearson-Spearman rank correlation. Results: A strong correlation between SUA level with systolic blood pressure (SBP) in patients with primary HTN (r = 0.5046; P < 0.0001) was observed. The mean SBP (163.89 ± 9.99 mmHg) was significantly high (P < 0.001) in hyperuricemic patients, and raised SUA was noted in 38% of the cohort. Stage II hypertensive subjects of the 58-66 years age group were found to be a particularly vulnerable group (odds ratio of 32). History of diabetes mellitus, tobacco, and alcohol consumption showed a significant association with elevated SUA levels in males (P < 0.05). Conclusion: One in every three primary hypertensive patients is likely to present with hyperuricemia, and there exists a pertinent association between elevated SUA levels with SBP.